Analysis Of Tax Disputes On Loans From Shareholders: A Case Study On Tax Court Rulings For The Period 2018-2022 - Parmalia, Indah; Rosid, Arifin (Journal Research of Social Science, Economics, and Management, 2023)
This research aims to analyze the causes of tax disputes over loans from shareholders. This research is also intended to provide recommendations for minimizing the occurrence of tax disputes over loans from shareholders. This research is qualitative research with a case study approach and was carried out using content analysis of tax court decisions and analysis of interviews with the Fiscus and Taxpayers. Loan disputes from shareholders consist of formal disputes and material disputes. The results of this research show that formal loan disputes from shareholders occur due to the implementation and application of tax regulations, while material disputes relate to loan terms, debt ratios and interest rates. Therefore, this research provides a solution for the Directorate General of Taxes (DGT) and Taxpayers to reduce loan disputes from shareholders occurring again. DGT can make policies and regulations related to cash pooling and loan interest rates. Solutions that can be given to taxpayers are holding training and Focus Group Discussions (FGD) related to taxation, holding meeting or actively consulting with Account Representatives (AR), paying attention to formal provisions for transactions even though they are carried out between companies of the same group. The limitation of this research is that there is still decision data that is not included in this research and there is decision data that cannot be read because the decision results are the results of manual scans downloaded from the Tax Court website.